Fitoremediasi Tanah Tercemar Logam Hg, Cr, As Menggunakan Tanaman Akar Wangi (Vetiveria Zizanioides) di TPA Lama Tempat Pemrosesan Akhir Talang Gulo Provinsi Jambi - Destri, Melly; Yanova, Shally; Jalius, Jalius (Al-Ard: Jurnal Teknik Lingkungan, 2024)
The soil polluted by heavy metals in the old Talang Gulo TPA has been a waste disposal site for many years, so that the surrounding soil is contaminated with the heavy metals mercury, chromium and arsenic. For this reason, it is necessary to know the concentrations of heavy metals Hg, Cr, As, and to test the effectiveness of vetiver (Vetiveria zizanioides) in reducing the content of Hg, Cr, and As metals in polluted soil in the old TPA Talang Gulo Jambi TPA. The research method was in the form of a preliminary survey with the type of research being carried out in an experimental manner, to restore heavy metal polluted soil using the phytoremediation method using vetiver (Vetiveria zizanioides). The results showed that the height and weight growth of Vetiveria zizanioides based on the results of ANOVA statistical calculations showed that Vertiveria zizanioides plants did not differ significantly in plant growth between polluted soil and control soil. As well as the effectiveness of vetiver (Vetiveria zizanioides) in reducing the metal content of Hg, Cr, As, in TPA Talang Gulo Jambi. Shows a decrease in metal content that occurred for 8 weeks. The absorption of metal mercury (Hg) is T1 0.606 mg/kg (56%), T2 0.599 mg/kg (57%), T3 0.544 mg/kg (60%), T4 0.324 mg/kg (76%) on chromium metal (Cr) of T1 1.348 mg/kg (39%), T2 1.248 mg/kg (44%) , T3 1.078 mg/kg (51%), T4 0.759 mg/kg (76%), and in arsenic metal (As ) T1 0.904 mg/kg (46%), T2 0.759 mg/kg (55%), T3 0.685 mg/kg (59%), T4 0.589 mg/kg (65%).